An Intelligent Method for Expert Finding Based on Knowledge Organization Systems: Taking the Example of Oncology. Issue 2 (June 2019) - Pei-yan, Song; Dong-fang, Wang; Yan, Cao
Abstract: In this paper, the experts are mapped and found through the concept and semantic relations of knowledge organization systems. First, a hierarchical model of expert description is designed based on the literature data and knowledge organization systems, as foundation of expert rapid finding, intelligent reasoning and dynamic updating. Then, 5 key steps are introduced based on knowledge organization systems, by which the research directions of experts can be identified accurately and visually in TF-IDF and LDA model. Finally, taking the example of Oncology, the experiment indicates that experts with the same or near research direction can be aggregated fast and effectively by semantic linkage compared with VSM agritourism. This method is expected to find out the most suitable experts by calculation and reasoning automatically.